Challenging neurovascular coupling through complex and variable duration cognitive paradigms: A subcomponent analysis. (December 2022) - Ladthavorlaphatt, Kannaphob; Surti, Farhaana B.S.; Beishon, Lucy C.; Panerai, Ronney B.; Robinson, Thompson G.
Highlights: The influence of peripheral haemodynamics on the integrity of neurovascular coupling response to complex and variable duration cognitive tasks has not been studied previously. Cerebral blood flow velocity was decomposed for determining subcomponents of underlying mechanisms. Neurogenic and myogenic contributions responded with similar temporal patterns for all task activations. Metabolic parameter showed differences related to complexity or duration of naming word paradigm. Peripheral haemodynamics have a major contribution to cognitive activation in subjects, based only on their cerebral blood flow velocity response to stimulation. Abstract: A similar pattern of cerebral blood velocity (CBv) response has been observed for neurovascular coupling (NVC) assessment with cognitive tasks of varying complexity and duration. This lack of specificity could result from parallel changes in arterial blood pressure (BP) and PaCO2, which could confound the estimates of NVC integrity. Healthy participants ( n = 16) underwent recordings at rest (5 min sitting) and during randomized paradigms of different complexity (naming words (NW) beginning with P-, R-, V- words and serial subtractions (SS) of 100–2, 100–7, 1000–17, with durations of 5, 30 and 60 s). Bilateral CBv (middle cerebral arteries, transcranial Doppler), end-tidal CO2 (EtCO2, capnography), blood pressure (BP, Finapres) and heart rate (HR, ECG) were recorded continuously. The bilateral CBv response to all paradigms was classified under objective criteria to select only responders, then the repeated data were averaged between visits . Bilateral CBv change to tasks was decomposed into the relative contributions (subcomponents) of arterial BP (VBP ; neurogenic), critical closing pressure (VCrCP ; metabolic) and resistance area product (VRAP ; myogenic). A temporal effect was demonstrated in bilateral VBP and VRAP during all tasks ( p <0.002), increased VBP early (between 0 and 10 s) and followed by decreases of VRAP late (25–35 s) in the response. VCrCP varied by complexity and duration ( p <0.046). The main contributions to CBv responses to cognitive tasks of different complexity and duration were VBP and VRAP, whilst a smaller contribution from VCrCP would suggest sensitivity to metabolic demands. Further studies are needed to assess the influence of different paradigms, ageing and cerebrovascular conditions.